Growth performance and antioxidant enzyme activities in rainbow trout (Oncorhynchus mykiss) juveniles fed diets supplemented with sage, mint and thyme oils - Sonmez, Adem Yavuz; Alak, Gonca; Bilen, Soner; Hisar, Olcay; Yanik, Talat; Biswas, Gouranga (Springer Science and Business Media LLC, 2014)
This study evaluated effects of dietary supplementation of sage (Salvia officinalis), mint (Mentha spicata) and thyme (Thymus vulgaris) oils on growth performance, lipid peroxidation level (melondialdehyde, MDA) and liver antioxidant enzyme activities (superoxide dismutase, SOD; catalase, CAT; glucose-6-phosphate dehydrogenase, G6PD; glutathione reductase, GR; glutathione-S-transferase, GST and glutathione peroxidase, GPx) in rainbow trout (Oncorhynchus mykiss) juveniles. For this purpose, triplicate groups of rainbow trout were fed daily ad libitum with diets containing sage, mint and thyme oils at 500, 1,000 and 1,500 mg kg(-1) for 60 days. While weight gain percentage of fish fed the diets containing sage and thyme oils was significantly higher than the control group, that of fish fed mint oil was the lowest. Similarly, specific growth rate was found to be the highest in all groups of the sage and thyme oil feeding and the lowest in the mint groups. Moreover, feed conversion ratio was significantly higher in the mint oil administered groups. Survival rate was also significantly reduced in the fish fed the diet containing mint oil. It was observed that SOD, G6PD and GPx activities were significantly increased in liver tissues of all the treated fish groups compared to that of control diet-fed group. However, CAT, GST and GR activities were significantly decreased in experimental diet-fed fish groups at the end of the experiment. On the other hand, a significant reduction was found in MDA levels in the fish fed the diets with sage and thyme oils compared to control and mint diets on the 30th and 60th days of experiment. Overall, dietary inclusion of sage and thyme oils is effective in enhancing rainbow trout growth, reduction in MDA and least changing antioxidant enzyme activities at a low level of 500 mg kg(-1) diet, and they can be used as important feed supplements for rainbow trout production.
Keywords: Analysis of Variance; Glutathione Peroxidase; Superoxide Dismutase; Body Weight; Glucosephosphate Dehydrogenase; Catalase; Thymus Plant; Glutathione Reductase; Spectrophotometry; Oncorhynchus mykiss; Dietary Supplements; Animals; Plant Oils; Lipid Peroxidation; Salvia officinalis; Glutathione Transferase; Mentha; 3. Good health